Key attributes of designers' competency for prevention through design (PtD) practices in construction: a review. Issue 4 (14th July 2020) - Che Ibrahim, Che Khairil Izam; Belayutham, Sheila; Manu, Patrick; Mahamadu, Abdul-Majeed
Abstract : Purpose: Designers have a key role to play in the Prevention through Design (PtD) practices in construction projects. Nonetheless, previous studies indicated that the issue of competencies to perform and sustain such practices over time is of a significant concern. This study aims to explore the key attributes of designers' competencies for PtD practices in construction. Design/methodology/approach: By using the Scopus database, a total of 86 papers related to PtD in construction published in peer-reviewed journals were reviewed and analysed using the well-established systematic literature review (SLR) methodology. Findings: The review indicates that in order to be competent in PtD implementation, designers need to be equipped with tacit and explicit knowledge, technical and soft skills and experience related to PtD. Furthermore, the review identifies attributes of these competencies. Additionally, a framework that links key PtD elements/principles with the PtD competencies is presented. Practical implications: The findings would enable contribution to the industry by providing the necessary references for design organisations to improve their designers' PtD competencies and hence, be able to meet their responsibility under relevant occupational safety and health (OSH) legislative framework. Originality/value: This study extends the PtD literature in the construction context by providing deeper insights into the conceptualisation of relationship between competent designers and PtD elements. The novelty also lies in the consolidation of PtD competency attributes for designers in construction that could act as a reference for any future developments related to PtD competency assessment for designers.